A new spirit [videorecording (DVD)] - Damkani, Jacob, 1952-; Biton, Imri; Shachar, Ohad, 1957-; Ben-David, Doron; Damkani, Jacob, 1952- (Vision Video, 2023)
Inspired by the best-selling autobiography "Why Me" by Jacob Damkani, this film tells the story of two brothers, Jacob and Shmuel, who grew up in a poor, traditional Jewish family. As they mature, Shmuel becomes more orthodox and religious while Jacob is exposed to Christianity and ends up becoming a leader of Messianic Judaism, spreading the word of Jesus.